PENTINGNYA MANAJEMEN AKUNTANSI SUMBER DAYA MANUSIA - Mutiara Kemala Ratu; Vhika Meiriasari; Kgs. M. Nurkholis (Universitas Indo Global Mandiri, 2022)
Accounting still seems to be growing more widely until now. One thing which is disputed is the Human Resource Accounting. Human Resources Accounting (HRA) was born because some experts feel that the human resources is an asset to the company and not a burden as in conventional accounting. Human resources is an enforcer for the company which has the most important role for a company. Because of human resources, the company will be able to get high profits, the operation go smoothly, and can get other corporate goals. Therefore, human resources ought to be used as a corporate asset so companies need to implement Human Resources Accounting.